Sustainable development and specific vulnerabilities generated by the lack of basic needs - Assis, Wilma de; Zanella, Maria Elisa (Revista Brasileira de Pós-Graduação, 2014)
This study was conducted within the framework of the transition, or attempted transition, from a model of development considered unsustainable to one characterized by sustainability. The analysis of this transition is based on the presence of international organizations that work towards the humanization of the development process and the existence of new indices of development. The main objective is to identify the potential social or individual vulnerabilities generated by the lack of basic needs. The study approaches this question through an overlap of the concepts of development, needs, and vulnerabilities, drawing on a number of methodological procedures derived from the Complexity Theory. The results of the study indicate the need for economic approaches to assimilate the complexity of the problem, using new indices of sustainability and human values. In particular, the study concludes that when the economy changes, the development process also changes. When human beings change, the economy and development also change.